Linguistic and psychological-pedagogical aspects of foreign languages teachers and lecturers training: innovative approaches - Melnyk, O. V.; Huryna, N. V. (Видавництво НДУ ім. М. Гоголя, 2025)
The aim of the article is a complex analysis of the linguodidactic and psychological-pedagogical aspects of training foreign language teachers in the context of modern trends in the educational process. Special attention is paid to integrating innovative methods and approaches aimed at the formation of teachers’ professional competence. Methodology: Linguodidactic aspects providing a methodological basis for the defining of innovative approaches to teaching foreign languages demanded a thorough qualitative research of studies on modern communicative methods, project activities, the use of information and communication technologies (ICT), and interactive learning that prevail in the methodology of FL at the present stage. The psychological-pedagogical aspects of foreign languages teachers training in the light of modern trends involved the critical analysis of modern emotional intelligence development researches, as well as studies on creating a motivational environment, reflection, and management of the educational process. Scientific novelty: The study proposes for the first time the integration of linguodidactics, psychological, and pedagogical aspects of foreign language teachers’ training that highlight innovative approaches to intercultural competence formation. The research paper emphasizes the need to form a critical thinking, reflective culture in teachers to provide their ability to self-regulate in a dynamic educational environment. Conclusions: integration of modern linguodidactic and psychological-pedagogical approaches in training foreign language teachers contributes to their professional mobility, ability to self-development, and successful implementation in changing educational realities. Combining theoretical knowledge with practical skills contributes to improving the quality of educational services. The use of modern technologies, such as online resources, distance learning platforms, and mobile applications for language learning, is a key aspect of preparing teachers for work in the digital age.
Keywords: linguodidactics; psychological-pedagogical training; foreign language teacher; professional competence; interactive methods; innovative approaches; intercultural competence; information and communication technologies; emotional intelligence; critical thinking; reflective culture